Monitoring, by high‐performance liquid chromatography, near‐infrared spectroscopy, and color measurement, of phytonutrients in tomato juice subjected to thermal processing and high hydrostatic pressure. Issue 5 (10th March 2021) - Ibrahim, Ayman; Daood, Hussein; Friedrich, László; Hitka, Géza; Helyes, Lajos
Abstract: Tomatoes are consumed as fresh and processed products, which contain nutritionally important phytonutrients. It is necessary to use a rapid and reliable analytical method to monitor the quality of tomato products. The study was conducted to study the feasibility of near‐infrared spectroscopy (NIRS) and color measurement with data obtained from high‐performance liquid chromatography (HPLC), for monitoring the change in tomato juice, as a consequence of thermal and high hydrostatic pressure (HHP) treatments at different conditions. Partial least squares regression was applied to assess the correlation between HPLC values of ascorbic acid (A.A.), lycopene (Lyc.), β‐carotene (β‐car.), and NIRS. The correlation was confirmed with R 2 P of .82, .92, and .91 based on the lowest values of the standard error of prediction (SEP) for A.A., Lyc., and β‐car., respectively. The lowest degradation of A.A. (35% and 49%), Lyc. (12% and 3.6%), and β‐car. (23.3% and 18.4%) was recorded for juice thermally processed and HHP treated, respectively. Novelty impact statement: Overdosage of food processing methods and exposure times generate food products that are poor in nutritional value. The results confirmed the ability of the near‐infrared spectroscopy to determine, measure, and predict the internal quality characteristics (ascorbic acid, lycopene, and β‐carotene) values of processed tomatoes and choose the best treatment methods and doses that afford the best quality to the final product. With increasing consumer awareness and market needs for healthy, and high nutritional value foods, the food industry will have profited from the nondestructive methods for quality detection, which in turn will determine the best processing methods, the optimum dosages, and the appropriate exposure time for processing. Hence, this technique is beneficial to produce high nutritional value food products able to meet the market needs, competition, and consumer satisfaction.